Handbook of Nanoparticles - Aliofkhazraei, Mahmood (Springer International Publishing : Imprint: Springer, 2016)
This Handbook covers all aspects of Nanoparticles, from their preparation to their practical application. The chapters present different ways to synthesize nanometer particles, as well as their functionalization and other surface treatments to allow them to a practical use. Several industrial applications of such nanometer particles are also covered in this Handbook. It is a complete reference for those working with Nanotechnology at the lab level, from students to professionals.